Pengembangan Media Video Berbasis Karakter Peduli Dan Kasih Sayang Pada Pembelajaran Tematik Terpadu Di Sekolah Dasar Islam Terpadu 1 Adzkia Kota Padang - Zuleni, Elva; Sisla Wati, Sisla Wati (LP2M Universitas Adzkia, 2023)
This is not in line with the goals of national education, one of which is to form children who have noble character. The videos used by schools as learning media do not yet contain character values. Based on this, a video of Sub-theme 2 Learning Human Growth and Development, 2 and 3. The purpose of the study was developed was to produce a character-based learning video. This research method is research and development (Research and Development). The development model used is a 4-D model consisting of four stages, namely defining and designing. Development (Developmnet) and dissemination (Dissemination). Based on the research, overall the average value of validation in the aspects of design, language and material is 91.01%. Then the practicality and effectiveness stages are carried out. This practicality stage is carried out on one educator and fifteen students. The practicality of the educator's response was obtained with a score of S8.8 o in the very practical category. While the practicality of the students' responses was obtained 79.08% with practical category. In the effectiveness stage, five educators and fifteen students were conducted. The effectiveness of the teacher's response was obtained by a value of 93.06% in the very effective category, while the effectiveness of the student's response in the